Correlation of Pregnant Women’s Knowledge of Purine Intake with Uric Acid Levels - Gusti Ayu Dhanu Wantari Dewi; Ni Luh Gede Puspita Yanti; Lia Cahya Sari (CV. CENDIKIA JENIUS INDONESIA, 2026)
Backgroud: Uric acid is the final product of purine metabolism, and one of the factors contributing to elevated uric acid levels is excessive purine consumption. High purine intake can increase the production of uric acid in the body. The prevalence of elevated uric acid levels in pregnant women is still common and, in advanced clinical conditions, may lead to preeclampsia. This may occur because during the second and third trimesters of pregnancy there is a decrease in glomerular filtration rate due to changes in renal function. Objective: To determine the relationship between the level of knowledge of pregnant women regarding purine intake and uric acid levels at UPTD Puskesmas III North Denpasar. Methods: This study was an analytical observational study with a cross-sectional approach. The sample consisted of 56 pregnant women in the second and third trimesters selected using accidental sampling technique. Data on the level of knowledge regarding purine intake were obtained through a questionnaire, while uric acid levels were measured using capillary blood examination with the Point of Care Testing (POCT) method. Results: The results showed that 62.5% of pregnant women had good knowledge and 71% had normal uric acid levels. The Spearman Rank correlation test showed a significance value of p = 0.000 and a correlation coefficient of r = 0.915. Conclusion : There is a significant relationship between pregnant women's knowledge about purine intake and uric acid levels, and it shows a very strong positive direction. Pregnant women are advised to be selective in choosing the foods they consume to prevent an increase in uric acid levels during pregnancy.